The Septuagint of Jeremiah a study in translation technique and recensions - Tucker, Miika; Vandenhoeck & Ruprecht (Göttingen Vandenhoeck & Ruprecht, 2022)
Miika Tucker comprises a translation technical study of the Septuagint version of Jeremiah for the purpose of characterizing the translation. The conclusions draw from different types of changes that occur between chapters 1–28 (Jer a’) and 29–52 (Jer b’). Certain differences between the two reflect the revisional characteristics of the kaige tradition, which suggests that they were produced by a reviser who was invested in a revisionary tradition similar to kaige. Other differences constitute a change toward more natural Greek expression, which is the opposite of what one would expect from a revision since Greek idiom usually does not correspond to the formal characteristics of Hebrew. Such differences are to be understood to reflect a change toward more intuitive use of the Greek language by the first translator. Changes toward less formal equivalence of the Hebrew and the growth of the Hebrew text after the initial translation combined to form conducive conditions for revision.
Angaben zur beteiligten Person Tucker: Miika Tucker recently completed his doctorate in Theology with distinction at the University of Helsinki. He is a long-time member of the Society of Biblical Literature, the International Organization for Septuagint and Cognate Studies, and the Finnish Exegetical Society. Miika is a postdoctoral researcher at the University of Helsinki, and he studies the textual history of the Book of Jeremiah. He is the editor of the forthcoming Jeremiah volumes in the Biblia Hebraica Quinta edition and The Hebrew Bible: A Critical Edition.
Angaben zur beteiligten Person Aejmelaeus: Anneli Aejmelaeus ist Professorin für Altes Testament und vorderasiatische Kultur und Literatur an der Universität Helsinki.
Angaben zur beteiligten Person Albrecht: Felix Albrecht (Dr. theol., geb. 1981) forscht seit 2008 an der Göttinger Akademie der Wissenschaften zur Septuaginta, das ist die griechische Übersetzung des hebräischen Alten Testaments. Seit Beginn des Jahres 2020 leitet er das Akademievorhaben "Editio critica maior des griechischen Psalters". Zudem ist er Vorstandsmitglied und Secretary der International Organization for Septuagint and Cognate Studies. Im Zentrum seines Interesses steht die griechische Bibel im Kontext des hellenistischen Judentums mit ihrer Rezeptions- und Transmissionsgeschichte. Daneben pflegt er eine Vorliebe zum Christlichen Orient und befasst sich intensiv mit Handschriftenforschung, Künstlicher Intelligenz und Digital Humanities.
Angaben zur beteiligten Person Troyer: Dr. Kristin De Troyer ist Professorin für Altes Testament/Hebräische Bibel am St Mary's College, St Andrews.
Angaben zur beteiligten Person Kraus: Dr. Wolfgang Kraus ist Professor für Neues Testament an der Universiät des Saarlands, Saarbrücken.
Keywords: Exegese; Textübersetzung; Jeremia; Altes Testament; Hochschulschrift